Big Data em conteúdo espontâneo não-estruturado da internet como estratégia organizacional de orientação para o mercado - Corrêa Junior, Dirceu Silva Mello (Universidade do Vale do Rio dos Sinos, 2018)
Big Data is a social reality with growing business impact. However, a survey of US executives of large corporations identified a low capacity to effectively exploit this competitive intelligence opportunity in their companies. In order to deepen the understanding of this context, from the perspective of Market Orientation, the present dissertation presented an exploratory analysis about the current capacity of large companies with national performance in absorbing Big Data value, focusing their attention on a type of content, called Unstructured Data. As a result, it was identified that the companies studied are in a peculiar moment for the modern management of Market Orientation, a sort of evolutionary process and of transition in the understanding and use of this deluge of data. This moment of adaptation is further reinforced by a trend towards the use of more spontaneous data from consumers. In this study, five dimensions of this peculiar moment are presented, systematically addressing questions related to internal organization; suppliers and investment profiles; internal adaptations; among other strategic findings. Afterwards, the current path to the understanding of Big Data is also detailed, based on the possible practices identified in this business context.
Keywords: Big Data; Data Culture; Dados Não-Estruturados; Analytics; Orientação para o Mercado; Big Data; Data Culture; Unstructured Data; Analytics; Market Orientation; ACCNPQ::Ciências Sociais Aplicadas::Administração